KAHOOT! AND USERS’ VIEWS OF ISLAMIC JUNIOR HIGH SCHOOL IN YOGYAKARTA - Nenden Fujiya; Muhamad Nazarudin Asyidiq (Program Studi Pendidikan Bahasa Inggris Institut Pendidikan dan Bahasa Invada, 2022)
The student motivation can be created from a novel learning experience such as implementing a modern game application to access the competence. This study identified students’ teaching and learning process in term of assessment emphasizing on a gamification approach construction surrounding to a student response category, called Kahoot! application games. The main objective of this analysis was to discover the influence of Kahoot! on motivation, engagement, studying outcome, and attitudes concerns to ICT integration in future learning experiences. Quantitatively, the study conducted to 28 students belonging to the 9th grade student of an Islamic Junior High School in Yogyakarta, Indonesia. The data collected by using a likert scale questionnaire survey whose validity was tested with r-table score 0,05. We used Kahoot! Games as an application tool in this research. This study has shown that a significant proportion of students are generally positive towards gamification approach used in educational activities, in general, and especially Kahoot! application games. Kahoot! contributed to more student engagement and enthusiasm, better learning performance, and more desire and willingness to try Kahoot game application in the world of learning experiences.This study recommended to all educators in every level of education to elevate the way of teaching to the new era of technology so the student was more engage to learn in teaching learning activities. This study also recommended to all students in Junior High School, Senior High school and University level. They can learn something more enthusiastic by this game.The originality of this study is that this study focus on Junior High School students in Indonesia, whereas the way in teaching and learning in Indonesia is definitely different with the other abroad students such curriculum and even the teacher way in teaching and the students’ learning. Moreover, this study also focus on how the student views’ in applying this game.